Complementary Therapies for Treating Survivors of Torture - Vargas, Claudia María; O’Rourke, Deborah; Esfandiari, Malshid (Refuge: Canada's Journal on Refugees, 2004)
The long-term consequences of torture are complex, multidimensional, and pervasive. Torture leaves indelible scars in the mind, body, and cultural world of survivors, compromising their health and well-being. A clearer understanding of biological, psychological, and socio-cultural mechanisms underlying these difficulties is emerging. Research findings on pain are relevant for those suffering from post-traumatic stress disorder (PTSD) and its associated chronic pain. Rehabilitation programs require crossdisciplinary knowledge and expertise, including of complementary therapies. This article explores the use of complementary therapies in which psychotherapy, in concert with either physiotherapy or bodywork, is offered. Case studies illustrate its application and potential benefits. The clinical experience in controlled circumstances suggests the thesis that complementary therapies advance the psychological and physical healing process.